RADIKALISME ISLAM: SEJARAH, KARAKTERISTIK, DAN DINAMIKA DALAM MASYARAKAT MULTIKULTURAL DI INDONESIA - Taufani Taufani (ASKETIK: JURNAL AGAMA DAN PERUBAHAN SOSIAL, 2019)
This study aims to elaborate the history, characteristic, and dynamics of Radical Islam group in Indonesia. Post New Order era has opened political opportunity for radical Islam group to colour the Islamic and political dynamics in Indonesia. This study concluded that radicalism teaching was not something new in Islamic history. Radical Islam group could flourish due to the political openness milieu post New Order Era as well as the infiltration of radical Islam teaching rooted in Middle East into Indonesian Islam. To anticipate the strengthening of Radical Islam group influence in Indonesia, the collaboration between the state and the populace are highly needed.